Analytic Hierarchy Process in Production Engineering: A Bibliometry Analysis - Michels, Guilherme de Sá, Carolina; Negrelli, Amabeli Quariniri; Gesuino, David Batista; Martins, Paulo João; Bristot, Vilson Menegon; Filho, Leopoldo Pedro Guimarães; Madeira, Kristian; Yamaguchi, Cristina Keiko (International Journal of Advanced Engineering Research and Science, 2020)
AHP (Analytic Hierarchy Process) tool stands out for its reliability and effectiveness, therefore, the objective of this research was to identify the scientific productions found in the electronic databases chosen by the author on the AHP tool. The date of publication covered by the survey comprises the periods from April 1992 to January 2018. The electronic bases used for the research were Scopus, Web of Science and Scielo, which after filtering only articles that mentioned the method in the title or abstract totaled in 178 articles. The year 2013 was the most productive with 24 articles (13.48%) published. Eight researchers appeared to be more productive because they had more than one published article. The International Journal of Production Research was the most productive periodical (5.62%), China the country with the largest number of publications (34.26%) and four universities had the largest number of articles published (6.74%) and the words that more appeared in article were process, hierarchy, analytic, fuzzy and production. It is concluded that the AHP tool still has great relevance in decision support methods even after 46 years of its creation, and that its potential continues to be promising for the analysis and solution of problems.